Jesus in context making sense of the historical figure - Wenham, David 1945- (Cambridge University Press, 2021)
Jesus changed our world forever. But who was he and what do we know about him? David Wenham's accessible volume is a concise and wide-ranging engagement with that enduring and elusive subject. Exploring the sources for Jesus and his scholarly reception, he surveys information from Roman, Jewish, and Christian texts, and also examines the origins of the gospels, as well as the evidence of Paul, who had access to the earliest oral traditions about Jesus. Wenham demonstrates that the Jesus of the New Testament makes sense within the first century CE context in which he lived and preached. He offers a contextualized portrait of Jesus and his teaching; his relationship with John the Baptist and the Qumran community (and the Dead Sea Scrolls); his ethics and the Sermon on the Mount, his successes and disappointments. Wenham also brings insights into Jesus' vision of the future and his understanding of his own death and calling
Title from publisher's bibliographic system (viewed on 03 Nov 2021)
Keywords: Jesus Christ / Historicity; Jesus Christ / Biography / Sources; Jesus Christus; Leben-Jesu-Forschung; Christologie